USING THE ERP SYSTEM IN THE PLANNING OF INVENTORY OF ENTERPRISES - Iskandarova D. H. (Galaxy International Interdisciplinary Research Journal, 2022)
In the conditions of a market economy, the planning of inventory of an enterprise with the use of innovations in information technologies becomes relevant. In this article, the author comprehensively considered the possibility of using the ERP system in the planning of inventory of industrial enterprises.